Facile and Sensitive Acetylene Black-Based Electrochemical Sensor for the Detection of Imatinib - Shun Li; Qingwu Tian; Xuanming Xu; Chao Xuan; Xiaomin Yang; Shukai Sun; Tingting Zhou (International Journal of Analytical Chemistry)
A facile and sensitive electrochemical sensor for determining imatinib (IMA) was constructed by modifying a glassy carbon electrode (GCE) with a nanocarbon material, acetylene black (AB). The electrochemical behavior of IMA on the prepared GCE/AB was studied using electrochemical techniques, namely, differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy. The direct determination of IMA by the GCE/AB sensor was accomplished using DPV under optimized conditions. The method verification showed that the oxidation peak current was proportional to the concentrations of IMA in the linear ranges of 0.01–0.5 and 0.5–4 μM, with correlation coefficients of 0.9856 and 0.9946, respectively. The limit of detection of the GCE/AB sensor was 0.15 nM. Moreover, the GCE/AB sensor showed good precision and accuracy. Finally, the GCE/AB sensor was successfully applied to determine IMA in human serum samples, and the recoveries were satisfactory.